Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1021/cm021087l
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Supramolecular Nanostructures Induced by Self-Assembly of Dendritic Building Blocks

Abstract: Dendrons with amide-urethane branch units and topochemically polymerizable diacetylene moieties at the alkyl periphery were synthesized via a convergent method. They form organized nanostructures in organic media and also in water. In organic media, they form lamella or columnar hexagonal structures depending on the dendron generation. By changing the solvent from organic to aqueous phase, the identical dendritic building blocks self-organize into a vesicular structure. The noncovalent interactions such as hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(34 citation statements)
references
References 27 publications
(8 reference statements)
1
33
0
Order By: Relevance
“…All synthesized poly(ferrocenophane)s exhibit electrochemical activity, and poly(ferrocenophane)s with different structures show distinguished cyclic voltammetry behavior [17][18][19][20], which will help us understand the relationship between structure, property and charge transfer mechanism, and benefit to design different functional modified electrodes. Dendritic molecules present a number of new possibilities in the areas of molecular engineering and nanotechnology due to their unique dendritic structure [21][22][23][24][25][26][27][28]. Thus, by incorporating dendritic molecules into poly(ferrocenylsilane)s polymer systems, one can potentially design a variety of functional organometallic polymer materials.…”
Section: Introductionmentioning
confidence: 99%
“…All synthesized poly(ferrocenophane)s exhibit electrochemical activity, and poly(ferrocenophane)s with different structures show distinguished cyclic voltammetry behavior [17][18][19][20], which will help us understand the relationship between structure, property and charge transfer mechanism, and benefit to design different functional modified electrodes. Dendritic molecules present a number of new possibilities in the areas of molecular engineering and nanotechnology due to their unique dendritic structure [21][22][23][24][25][26][27][28]. Thus, by incorporating dendritic molecules into poly(ferrocenylsilane)s polymer systems, one can potentially design a variety of functional organometallic polymer materials.…”
Section: Introductionmentioning
confidence: 99%
“…In an extension of this work, alkyne functionalities were incorporated into the long hydrophobic tails on the periphery of the dendritic structure [131]. TEM images of the second generation dendron indicated the presence of fibrous bundles, and X-ray diffraction (XRD) of the dried gels indicated that these fibres had a hexagonal columnar structure.…”
Section: Assembly Of One-dimensional Architectures Using Multiple Recmentioning
confidence: 91%
“…This type of 'covalent capture' strategy has been widely applied in dendrimer chemistry by Zimmerman and co-workers [21] and has been extended to the field of dendritic gels by our group, as well as that of Kim. [22] Dendritic surfaces are ideal for the covalent capture of nanoscale architectures because the multiplicity of the surface groups gives rise to a better chance of effective crosslinking. Clearly this strategy is somewhat similar to Grinstaff's use of peripheral polymerizable groups for the formation of crosslinked gels described above.…”
Section: Research Newsmentioning
confidence: 99%
“…Using this type of approach, Kim et al reported a dendritic gelator that has bis-alkyne groups on the periphery. [22] These groups undergo photoinitiated crosslinking when in close proximity to one another. Kim et al demonstrated that photoirradiation of their gels led to crosslinking of the gelphase material.…”
Section: Research Newsmentioning
confidence: 99%